The impact of social capital and social interaction on customers' purchase intention, considering knowledge sharing in social commerce context - Alireza Ghahtarani; Majid Sheikhmohammady; Mahdieh Rostami (Journal of Innovation & Knowledge (JIK), 2020)
In this research, we identify factors influencing the behavior of knowledge sharing and customer purchasing intention based on two theories of social capital and social interaction. The conceptual model, designed based on theoretical foundations, includes the dimensions of these two theories. Moreover, knowledge/information sharing is considered as a moderate variable and is attempted to examine the relationship between these variables and customers' purchase intention in the context of social commerce. Statistical sample is 254 individuals, who have bought more than 5 times from social commerce sites. The results show that the dimensions of social capital theory and social interaction theory have a significant relationship with knowledge/information sharing. Additionally, 'knowledge/information sharing' has a mediating role in the proposed model.
Keywords: 650; Customers' purchasing intention; Knowledge sharing behavior; Social capital; Social commerce; Social interaction theory